Global and domestic inequalities and the political economy of the midde-income trap - Svenja Flechtner; Stephan Panther (Cusanus Hochschule, Institut für Ökonomie und Institut für Philosophie, 2017)
Some middle-income economies, many of which Latin American, have not achieved to make the transition into high-income status for long years and are allegedly trapped in middle-income status. While there is considerable consensus on the proximate causes of this phenomenon, we present a global political economy perspective to the discussion, arguing that global and domestic inequalities, both political and economic, are key to understand the issue. We subject our argument to empirical scrutiny, using fuzzy-set qualitative comparative analysis (fsQCA) on data spanning the years 1976-2009. Both domestic economic equality and political independence from the influence of an external power turn out to be robust characteristics supporting growth convergence of middle-income countries.
Keywords: B52; D31; D63; F15; N36; O15; O29; O54; 330; inequality; independence; income distribution; distribution of wealth; dependence; Latin America